2022
DOI: 10.1039/d2cc00428c
|View full text |Cite
|
Sign up to set email alerts
|

A pressure-induced ratiometric signalling chemosensor: a case of helical anthracenes

Abstract: One of the helical anthracenes, [4]HA in which two fused anthracene ends are spatially arranged upper and lower, exhibits a ratiometric fluorescence response due to the hydrostatic pressure-dependent intramolecular [4+4]...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The former behavior originates from the pressure-induced solvent polarizability (density) changes that cause the stabilization of the π* orbital, , and the latter phenomenon occurs because of the increasing effective concentration during solution compression. Considering that the hydrostatic pressure effect on the bathochromic shift is generally observed at approximately 1 cm –1 MPa –1 for common π-conjugated organic molecules (such as anthracene, pyrene, and perylene), , the resulting shifts of 0 ∼ −0.39 cm –1 MPa –1 for 1Zn and −0.11 ∼ −0.25 cm –1 MPa –1 for 1Zn 2 were relatively small (Figures S6 and S9 in SI, respectively). This remarkable pressure effect was likely responsible for the characteristic Q-band obtained for the Pc chromophore, which revealed that the hydrostatic pressure responses in the Q-band were considerably different from those obtained for the regular π–π* transition.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The former behavior originates from the pressure-induced solvent polarizability (density) changes that cause the stabilization of the π* orbital, , and the latter phenomenon occurs because of the increasing effective concentration during solution compression. Considering that the hydrostatic pressure effect on the bathochromic shift is generally observed at approximately 1 cm –1 MPa –1 for common π-conjugated organic molecules (such as anthracene, pyrene, and perylene), , the resulting shifts of 0 ∼ −0.39 cm –1 MPa –1 for 1Zn and −0.11 ∼ −0.25 cm –1 MPa –1 for 1Zn 2 were relatively small (Figures S6 and S9 in SI, respectively). This remarkable pressure effect was likely responsible for the characteristic Q-band obtained for the Pc chromophore, which revealed that the hydrostatic pressure responses in the Q-band were considerably different from those obtained for the regular π–π* transition.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Many other applications are outside this Review because of its limited space and inability to cover all of them by a single author. Among them are the λ-ratiometric sensors for viscosity [139], temperature [140] and pressure [141] on a molecular scale. Detection of pathogenic bacteria [142], checking their drug resistance [143] and identifying the spores [144] benefit from using ratiometric fluorescence sensing.…”
Section: Fluorescentmentioning
confidence: 99%
“…In anthraquinone analog [3]HAq , we identified unusually short distances between the inner carbonyl oxygen atoms [12] . Additionally, we recently reported that [4]HA exhibits a ratiometric fluorescence response upon intramolecular [4+4] cycloaddition under high hydrostatic pressure [13] . Previous studies reveal that modifications to helical structures, particularly deformations along the helical axis akin to a mechanical spring, can significantly impact their properties and reactivity [6,14] .…”
Section: Introductionmentioning
confidence: 98%
“…[12] Additionally, we recently reported that [4]HA exhibits a ratiometric fluorescence response upon intramolecular [4 + 4] cycloaddition under high hydrostatic pressure. [13] Previous studies reveal that modifications to helical structures, particularly deformations along the helical axis akin to a mechanical spring, can significantly impact their properties and reactivity. [6,14] Cyclization of both ends of the helical moiety via a covalent bond offers a dependable method to compress the helical structure.…”
Section: Introductionmentioning
confidence: 99%